The role of the government in the management of tourism object development of kurenai beach botubarani village, Kabila Bone Bone Bolango regency - Lucyane Djaafar; Nopiana Mozin (International Journal on Social Science, Economics and Art, 2022)
Tourism development in Indonesia is one of the catalysts in supporting regional development and is expected to be a sustainable economic support in accordance with the government's work plan. This clearly requires encouragement from the community as well as support from the government in an effort to create world-class tourism development. Based on the above, the purpose of this study examines about " how the role of the government in the management of the development of Tourism objects Kurenai beach as well as inhibiting factors in the development of Tourism objects kurenai beach in Botubarani Kabila Bone Village Kab. Bone Bolango."The method used in this study is qualitative descriptive. The results found are the role of the government in the management of the development of Tourism objects Kurenai Beach Botubarani Village Kec. Kabila Bone Kab. Bone Bolango has not been maximized due to the entrance ticket/retribution that is misused by certain individuals to gain profit whereas if the entrance ticket/retribution is managed by the relevant government then it can be foreign exchange for the local government. Both related to the inhibiting factors in the development of kurenai beach attractions there has not been fully cooperation between the community and the local government, as well as the absence of a digital system, the website content created specifically to promote kurenai beach attractions itself, so it could make it difficult for visitors to find information related to what are the features of kurenai beach attractions in Botubarani village.